(untitled) (Research, Society and Development, 2023)
A large number of women have engaged in sports training for competitive purposes, whether amateur or professional in nature. There has been a significant increase in the participation of female athletes in Olympic games in the last 10 years. As a result, there has been an increase in interest in carrying out studies and research with the aim of evaluating the performance of female athletes in different modalities and aspects such as changes in strength, power and resistance. Therefore, the objective of this study is to evaluate the impacts of hormonal changes in the menstrual cycle on the performance of athletes with a normal menstrual cycle (eumenorrheic), as well as the influence of nutrition in managing the symptoms of these athletes’ cycle phases. Twenty-seven (27) scientific articles were selected for complete reading and recording, with the exclusion criteria being articles that referred to athletes who used oral, injectable or amenorrheic contraceptives. The studies carried out found that there are both positive and negative impacts of changes in the hormones estrogen and progesterone on athletes’ performance. These impacts can be emotional, physical, cognitive, metabolic, cardiovascular and musculoskeletal capacity. Despite the results observed, considering the wide variation in studies and research carried out so far, a general guideline has not been established regarding the management of these impacts in the training, competition and recovery stages of eumenorrheic athletes. Therefore, nutrition is essential in the intervention of symptoms and impacts in each phase of the menstrual cycle, as they can interfere with athletes’ performance.